On the Use of the Economic Concept of Human Capital in Financial Statements. - Lev, Baruch; Schwartz, Aba (The Accounting Review, 1971)
The dichotomy in accounting between human and nonhuman capital is fundamental, the latter is recognized as an asset and therefore is recorded in the books and reported in the financial statement, whereas the former is totally ignored by accountants. Most economists, on the other hand, have a different view on this issue. The definition of wealth as a source of in come inevitably leads to the recognition of human capital as one of several forms of holding wealth, such as money, securities, and physical, nonhuman, capital. This attitude toward human capital has a broad range of applications in economics. The objective of this article is to provide a practical measurement procedure by which some of the contradictory views given be economists on this issue could be clarified. Specifically, the possibility of using the economic concept and measurement of human capital in financial statements is explored. It is also shown that the suggested method provides decision makers with information about organizational matters hitherto not reported by accountants.